The Effect of Risk on the Firm's Optimal Capital Stock: A Note - Maloney, Kevin J.; Marshall, William J.; Yawitz, Jess B. (Journal of Finance, 1983)
In this paper we extend the recent work on the choice of input mix under uncertainty. In particular, we demonstrate that the qualitative nature of the disturbance term, along with the decision sequence, is a crucial determinant of the overall effect of uncertainty on the optimal input mix of a firm. Using general demand and production functions in conjunction with a mean-variance framework for financial valuation, we demonstrate the differential effects of systematic and non-systematic risk on the firm's choice of an optimal input mix. Consistent with earlier work in economics, this analysis demonstrates that uncertainty, regardless of the source, has important implications for the firm's choice of technology.